Tourism in Andalusia (Spain): an update from a geographical analysis - Garzón-García, Rafael; Ramírez-López, María Luisa; Vega-Pozuelo, Rafael; Florido-Trujillo, Gema (Revista de Estudios Andaluces, 2023)
The aim of the work is to offer an evolutionary and updated analysis of the tourism reality of the Autonomous Community of Andalusia (Spain). The proposed study is based on the use of the traditional quantitative variables (supply and demand) in their projection on a specific territorial space (Andalusia), of exceptional tourist relevance, but also of great complexity and diversity. It reflects on the value and representativeness of these variables for the territorial-tourist study, based on the official sources of information available, offering a proposal for specific indicators. For the case study, the important quantitative weight and general growth of tourism activity during the period analysed (2008-2022) is confirmed, which is accompanied by some certainly significant and interesting processes of change and restructuring, both in the internal conformation of supply and in certain patterns of demand behaviour.